1987
DOI: 10.3109/10826088709027486
|View full text |Cite
|
Sign up to set email alerts
|

Age of Onset, Periods of Risk, and Patterns of Progression in Drug Use Among American Indian High School Students

Abstract: A sample of 277 Native American students (grades 7 to 12) was surveyed to examine the age of onset, patterns of progression, and periods of risk for drug use. Results suggest that Native American youth begin smoking cigarettes and marijuana, drinking, sniffing solvents, and using cocaine as early as 10 years of age. The period of risk for initiation of drug use was between the ages of 10 and 13 years. Implications for drug use prevention-education programming are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…Other studies have identified early adolescence as a particularly risky period for initiation, specifically among Native American and African American youth. 9,35 The present study builds on these previous reports by examining the dynamic patterns and predictors of alcohol and marijuana initiation in a longitudinal sample. Given the role of adolescent onset in predicting later substance use problems, it is important to extend previous retrospective research by exploring prospectively when recent cohorts of young people are at the greatest risk for initiation and how this risk changes over the course of development.…”
Section: The Dynamics Of Alcohol and Marijuana Initiation: Patterns Amentioning
confidence: 98%
See 2 more Smart Citations
“…Other studies have identified early adolescence as a particularly risky period for initiation, specifically among Native American and African American youth. 9,35 The present study builds on these previous reports by examining the dynamic patterns and predictors of alcohol and marijuana initiation in a longitudinal sample. Given the role of adolescent onset in predicting later substance use problems, it is important to extend previous retrospective research by exploring prospectively when recent cohorts of young people are at the greatest risk for initiation and how this risk changes over the course of development.…”
Section: The Dynamics Of Alcohol and Marijuana Initiation: Patterns Amentioning
confidence: 98%
“…[2][3][4][5][6] Studies indicate that alcohol and marijuana use often begin early. 4,[7][8][9][10] In the 1997 Monitoring the Future Study, a nationwide survey, more than 54% of respondents reported that they had consumed alcohol, and 23% reported that they had used marijuana, by the eighth grade. 1 The age at which one first drinks alcohol or tries other substances is predictive of later problems with these substances, with earlier use placing individuals at greater risk for later abuse.…”
Section: The Dynamics Of Alcohol and Marijuana Initiation: Patterns Amentioning
confidence: 99%
See 1 more Smart Citation
“…The period of risk for drug use initiation among Indian youth is between the ages of 10 and 13 years, with the onset among some individuals being as young as 5 to 6 years of age (Okwumabua and Duryea, 1987). Inhalants, particularly gasoline, are used at an age earlier than any other substances (Thurman and Green, 1997;Mail and Johnson, 1993;.…”
Section: Agementioning
confidence: 99%
“…Tout dépendant des intérêts du chercheur, une caté-gorie plus spécifique apparaît parfois en ajout des trois précédentes, comme par exemple les facteurs sociopolitiques (Janosz et Leblanc, 1996), les facteurs socioéconomi-ques (Boyer, 1999;Quirouette et al, 1990;Radwanski, 1987), les facteurs interpersonnels (Janosz et al, 2000). (Kruger, 1995), la toxicomanie (Lin, 1985;Okwumabua et Duryea, 1987;Trimble et al, 1987), les comportements déviants (French, 1980, French et Hornbuckle, 1977Jones-Saumty et al, 1983;Lujan et 29 Par exemple, les facteurs liés à l'école (Hardy, 1994) sont nommés par d'autres facteurs organisationnels (Janosz et Leblanc, 1996), variables scolaires (Gélinas et al, 2000) ou facteurs institutionnels (Janosz et al, 2000). 30 Selon Kruger (1995), on a beaucoup moins étudié la problématique de la scolarisation chez les autochtones que chez tout autre minorité ethnique aux États-Unis, notamment les hispanophones et les Noirs.…”
unclassified